Attitudes of parents, teachers, and students of the Tabaco High School toward sex education and their implication to health education - Brondial, Gloria B. (s.n.], 1973)
This survey on attitudes toward sex education was made to determine the possibility of including sex education in the secondary school curriculum, most specially in health education, in the Tabaco High School.